The treatment of fashion in the cybermedia of Colombia and Spain: A comparison between el espectador, el tiempo, el país and ABC (2020)
In this article we address the construction of fashion journalism exercised by four referential cybermedia from Colombia and Spain, such as El Tiempo and El Espectador, and El País and ABC. To do this, by means of a content analysis, the analysis sheet of the VAP (Journalistic Added Value) has been used, with a sample of 904 articles published in 2016. © 2020, Associacao Iberica de Sistemas e Tecnologias de Informacao. All rights reserved.